2023
DOI: 10.1002/ece3.10474
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic response to different predator strategies can be mediated by temperature

Francesco Cerini,
Duncan O'Brien,
Ellie Wolfe
et al.

Abstract: Temperature change affects biological systems in multifaceted ways, including the alteration of species interaction strengths, with implications for the stability of populations and communities. Temperature‐dependent changes to antipredatory responses are an emerging mechanism of destabilization and thus there is a need to understand how prey species respond to predation pressures in the face of changing temperatures. Here, using ciliate protozoans, we assess whether temperature can alter the strength of pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…In contrast to the pollution treatment, the predator introduction, a press disturbance scenario, did not result in the predicted sequence of observable signals prior to a populations collapse. Whilst ciliates, and the Paramecium genus in particular, are known to display antipredatory behavioural and morphological responses (Cerini et al 2023b;Fyda et al 2005), neither behavioural nor morphological traits showed a clear pattern of change compared to the control in the predator treatment. Exposure to predatory Stenostomum cues induced a swimming speed reduction in Paramecium , and a cell shape change towards a ball-shape morph (to decrease likelihood of being engulfed by the predator, Hammillet al 2010b).…”
Section: Discussionmentioning
confidence: 90%
“…In contrast to the pollution treatment, the predator introduction, a press disturbance scenario, did not result in the predicted sequence of observable signals prior to a populations collapse. Whilst ciliates, and the Paramecium genus in particular, are known to display antipredatory behavioural and morphological responses (Cerini et al 2023b;Fyda et al 2005), neither behavioural nor morphological traits showed a clear pattern of change compared to the control in the predator treatment. Exposure to predatory Stenostomum cues induced a swimming speed reduction in Paramecium , and a cell shape change towards a ball-shape morph (to decrease likelihood of being engulfed by the predator, Hammillet al 2010b).…”
Section: Discussionmentioning
confidence: 90%